2012
DOI: 10.1007/s00216-012-6412-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling reveals new serum biomarkers for differentiating diabetic nephropathy

Abstract: Capillary electrophoresis coupled with time-of-flight mass spectrometry was used to explore new serum biomarkers with high sensitivity and specificity for diabetic nephropathy (DN) diagnosis, through comprehensive analysis of serum metabolites with 78 diabetic patients. Multivariate analyses were used for identification of marker candidates and development of discriminative models. Of the 289 profiled metabolites, orthogonal partial least-squares discriminant analysis identified 19 metabolites that could disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 24 publications
4
131
0
Order By: Relevance
“…Dried aqueous metabolites were reconstituted with 50 ml of Milli-Q water that contained two reference compounds (200 mM each of 3-aminopyrrolidine and trimesic acid). Samples were analysed using capillary electrophoresis-electrospray ionization (ESI)-time-of-flight mass spectrometry (TOFMS) in both positive and negative mode 39 . In brief, cationic metabolites were separated in a fused silica capillary (50 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…Dried aqueous metabolites were reconstituted with 50 ml of Milli-Q water that contained two reference compounds (200 mM each of 3-aminopyrrolidine and trimesic acid). Samples were analysed using capillary electrophoresis-electrospray ionization (ESI)-time-of-flight mass spectrometry (TOFMS) in both positive and negative mode 39 . In brief, cationic metabolites were separated in a fused silica capillary (50 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, metabolites are the final product of cellular processes, providing a direct link to phenotypes (1). For this reason, an increasing number of studies have been conducted to discover metabolites whose levels significantly change in a specific clinical condition (2)(3)(4). In a previous study, we identified a panel of 13 metabolites that were robustly altered in patients with diabetic nephropathy (3), thus motivating us to investigate the underlying molecular networks linked to these metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, CE also gives complementary information to HILIC [13], as well as, significantly better peak shape in many cases. It is therefore not surprising that CE-MS has already been considered for multiple metabolomics studies covering several applications, from aging [19], amino acid analysis [20,21] [46][47][48][49][50][51][52][53], CVD [54][55][56][57][58], diabetes [59][60][61][62][63][64][65], lifestyle [61][62][63][64][65][66][67][68][69][70][71], kidney disease [72,73], liver disease [74][75][76][77][78][79][80][81][82], the microbiome [83][84]…”
Section: Current Advantages and Biotechnology Applicationsmentioning
confidence: 99%